Inhibition of hERG potassium channel by the antiarrhythmic agent mexiletine and its metabolite m‐hydroxymexiletine. Issue 5 (31st July 2015) - Gualdani, Roberta; Tadini‐Buoninsegni, Francesco; Roselli, Mariagrazia; Defrenza, Ivana; Contino, Marialessandra; Colabufo, Nicola Antonio; Lentini, Giovanni
Abstract: Mexiletine is a sodium channel blocker, primarily used in the treatment of ventricular arrhythmias. Moreover, recent studies have demonstrated its therapeutic value to treat myotonic syndromes and to relieve neuropathic pain. The present study aims at investigating the direct blockade of hERG potassium channel by mexiletine and its metabolite m‐hydroxymexiletine (MHM). Our data show that mexiletine inhibits hERG in a time‐ and voltage‐dependent manner, with an IC50 of 3.7 ± 0.7  μ mol/L. Analysis of the initial onset of current inhibition during a depolarizing test pulse indicates mexiletine binds preferentially to the open state of the hERG channel. Looking for a possible mexiletine alternative, we show that m ‐hydroxymexiletine (MHM), a minor mexiletine metabolite recently reported to be as active as the parent compound in an arrhythmia animal model, is a weaker hERG channel blocker, compared to mexiletine (IC50  = 22.4 ± 1.2  μ mol/L). The hERG aromatic residues located in the S6 helix (Tyr652 and Phe656) are crucial in the binding of mexiletine and the different affinities of mexiletine and MHM with hERG channel are interpreted by modeling their corresponding binding interactions through ab initio calculations. The simulations demonstrate that the introduction of a hydroxyl group on the meta‐position of the aromatic portion of mexiletine weakens the interaction of the drug xylyloxy moiety with Tyr652. These results provide further insights into the molecular basis of drug/hERG interactions and, in agreement with previously reported results on clofilium and ibutilide analogs, support the possibility of reducing hERG potency and related toxicity by modifying the aromatic pattern of substitution of clinically relevant compounds.